The Secret Explorers and the rainforest rangers - King, SJ (King, SJ. Secret Explorers, 2021)
The Secret Explorers head to the Borneo rainforest on a mission to rescue a lost baby orangutan. Along the way, they learn about threats to the rainforest--especially from greedy plantation owners to want to cut down the rainforest to expand palm oil production.